2018
DOI: 10.21037/jtd.2018.09.61
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after pulmonary surgery

Abstract: Surgery implies the concept of "recovery" as a central pillar of the patient trajectory. It has been a focal point of surgical research for ages; however, the specific components that define surgical recovery are not well defined. Historically, measures such as perioperative mortality, morbidity, complications, and hospital length of stay have been used as proxies to define surgical recovery. This disconnect between the definition of recovery and the endpoints we use to measure recovery in research is well add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Improving HR-QOL is the other half, and as discussed PRO are the best way to measure this. In a recent review of ERAS in lung surgery patients, the notion of including PRO is emphasized (44). Eustache et al highlight the concept of postoperative recovery and "returning to baseline" after surgery.…”
Section: Using Pro In Eras Pathwaysmentioning
confidence: 99%
“…Improving HR-QOL is the other half, and as discussed PRO are the best way to measure this. In a recent review of ERAS in lung surgery patients, the notion of including PRO is emphasized (44). Eustache et al highlight the concept of postoperative recovery and "returning to baseline" after surgery.…”
Section: Using Pro In Eras Pathwaysmentioning
confidence: 99%
“…[ 8 ] Regarding thoracic surgery, there are different comparable ERATS protocols (with similar, but not the same recommendations) developed from different centers in different countries. [ 9 10 11 12 13 14 15 16 17 ] The Enhanced Recovery After Surgery (ERAS®) Society and the European Society of Thoracic Surgeons (ESTS) have subsequently developed an international “formal” consensus on ERATS. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is now very well documented in the literature that VATS offers significant advantages over open thoracotomy. [2][3][4][5][6][7][8][9][10][11][12][13][17][18][19][20] However, most of these studies still reported median LOS between 4 and 7 days for patients undergoing VATS lobectomy. In the fall of 2015, our centre became a regional thoracic surgical oncology referral site exclusively servicing a catchment area with a population upwards of 2 million and a geographic area covering half the area of the province of Quebec (approximately 680 000 km 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most contemporary series on VATS lobectomy report a median LOS of between 4 and 6 days after the procedure. 17,18 Although LOS is a problematic metric in comparisons of centres, particularly because of the impact of socioeconomic factors and health care system differences, the prospect of moving toward shorter hospital stays and earlier return to function after VATS lobectomy is an attractive one. [19][20][21] Indeed, from the perspective of ERP after surgery, earlier return home and earlier return to baseline function may further support the use of surgery to treat lung cancer or pulmonary metastasis, particularly in the age of competing emerging nonsurgical ablative therapies.…”
mentioning
confidence: 99%